2015
DOI: 10.1371/journal.pone.0138425
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta (TGF-β) Is a Muscle Biomarker of Disease Progression in ALS and Correlates with Smad Expression

Abstract: We recently identified Smads1, 5 and 8 as muscle biomarkers in human ALS. In the ALS mouse, these markers are elevated and track disease progression. Smads are signal transducers and become activated upon receptor engagement of ligands from the TGF-β superfamily. Here, we sought to characterize ligands linked to activation of Smads in ALS muscle and their role as biomarkers of disease progression. RNA sequencing data of ALS muscle samples were mined for TGF-β superfamily ligands. Candidate targets were validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 36 publications
15
56
0
Order By: Relevance
“…1C). As expected, the satellite cell marker Pax7 (Seale et al, 2001) was nearly absent from the TA muscle ribosomal mRNA fractions compared with total muscle mRNA (Fig. 1C).…”
Section: Muscle Fibers Express and Concentrate Fgfbp1 At Nmjssupporting
confidence: 82%
See 1 more Smart Citation
“…1C). As expected, the satellite cell marker Pax7 (Seale et al, 2001) was nearly absent from the TA muscle ribosomal mRNA fractions compared with total muscle mRNA (Fig. 1C).…”
Section: Muscle Fibers Express and Concentrate Fgfbp1 At Nmjssupporting
confidence: 82%
“…Heterozygous animals were intercrossed to produce the homozygous mutant FGFBP1 Ϫ/Ϫ animals. The following mice were obtained from The Jackson Laboratory: SOD1 G93A (RRID:IMSR_JAX:004435; Gurney et al, 1994), Parvalbumin-Cre (RRID:IMSR_JAX:017320; Hippenmeyer et al, 2005; referred to herein as PVCre), Thy1-YFP16 (RRID:IMSR_JAX:003709; Feng et al, 2000; referred to herein as THYFP16), and RiboTag (RRID: IMSR_JAX:011029;Sanz et al, 2009) mice. To visualize motor axons, THYFP16 mice were crossed with SOD1 G93A , FGFBP1 Ϫ/Ϫ , and SOD1 G93A ;FGFBP1 Ϫ/Ϫ mice.…”
Section: Animalsmentioning
confidence: 99%
“…We and others [37] have found augmented levels of TGF-β (three isoforms) in symptomatic hSOD1G93A mice. The pro-fibrotic effect of TGF-β1 have been well-studied, however, controversial evidence regarding TGF-β3 exist.…”
Section: Discussionmentioning
confidence: 73%
“…This pathway plays a very important role as a downstream mediator of muscle wasting 33,34 . Additionally, TGF-β1 mRNA and protein expression are significantly increased in skeletal muscles of humans and mice with ALS, and because of this characteristic, TGF-β1 could be used as a muscle biomarker for ALS disease 10 . Previous studies have shown that AMPK activation can prevent muscle wasting induced by inflammation through inhibition of the iNOS/NO pathway 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Especially, TGF-β1 level was elevated in the serum and plasma of ALS patients 8 . Also, other studies showed that the TGF-β family were significantly increased in human and mice ALS muscle tissue and suggested that TGF-β family could be strong marker of disease progression and onset 9,10 . Especially, oxidative stress induced by TGF-β1 in the skeletal muscle is essential feature of ALS muscle pathology 11 .…”
mentioning
confidence: 95%